2008
DOI: 10.1097/aln.0b013e31816d83e4
|View full text |Cite
|
Sign up to set email alerts
|

STOP Questionnaire

Abstract: The STOP questionnaire is a concise and easy-to-use screening tool for OSA. It has been developed and validated in surgical patients at preoperative clinics. Combined with body mass index, age, neck size, and gender, it had a high sensitivity, especially for patients with moderate to severe OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
401
2
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,819 publications
(421 citation statements)
references
References 42 publications
10
401
2
5
Order By: Relevance
“…Major risk factors for OSA include male gender, obesity (body mass index >35 kg/m 2 ), wide neck (neck circumference > 40 cm), crowded oropharynx, and craniofacial abnormalities affecting the upper airway [62]. A four-question questionnaire known as “STOP” has been validated in screening perioperative patients for OSA [63]. Patients at risk for OSA should be asked the following four questions:

Snore: Do you snore loudly?

Tired: Do you often feel tired, fatigued, or sleepy during the day?

Observed: Has anyone observed you stop breathing during your sleep?

Blood pressure: Do you have or are you being treated for hypertension?

…”
Section: Risk Factors For Ppcsmentioning
confidence: 99%
“…Major risk factors for OSA include male gender, obesity (body mass index >35 kg/m 2 ), wide neck (neck circumference > 40 cm), crowded oropharynx, and craniofacial abnormalities affecting the upper airway [62]. A four-question questionnaire known as “STOP” has been validated in screening perioperative patients for OSA [63]. Patients at risk for OSA should be asked the following four questions:

Snore: Do you snore loudly?

Tired: Do you often feel tired, fatigued, or sleepy during the day?

Observed: Has anyone observed you stop breathing during your sleep?

Blood pressure: Do you have or are you being treated for hypertension?

…”
Section: Risk Factors For Ppcsmentioning
confidence: 99%
“…In the 2014 survey, we included the STOPBANG questionnaire and measured neck circumference to the nearest centimeter using a tape measure by trained field workers to screen individuals at high risk of OSA 21. Questions in STOPBANG comprised eight binary variables, including snoring, daytime tiredness, observed apneas, blood pressure, body mass index (BMI) (>35 kg/m 2 ), age (>50 years), neck circumference (>40 cm), and sex (men).…”
Section: Methodsmentioning
confidence: 99%
“…Questions in STOPBANG comprised eight binary variables, including snoring, daytime tiredness, observed apneas, blood pressure, body mass index (BMI) (>35 kg/m 2 ), age (>50 years), neck circumference (>40 cm), and sex (men). Intermediate or high risk of OSA was defined as three or more of the eight items scored positive 21. Previous validation studies among different populations, including Chinese, showed a high sensitivity (91–94%) to detect OSA 22.…”
Section: Methodsmentioning
confidence: 99%
“…18 Longitudinal data collected by the Wisconsin Sleep Cohort Study over a 4-year period have shown that weight change is an important determinant of disease progression and regression. 5,8,14 Compared with participants with a stable weight, those that have a 10% increase in their weight had a 32% increase in their AHI and a six-fold risk of developing moderate to severe OSAHS.…”
Section: Introductionmentioning
confidence: 99%
“…It was an outcome of the Conference on Sleep in Primary Care in April 1996 in Berlin, Germany. 13,14 It includes 11 questions organized into the three categories, 5 questions related to snoring and the cessation of breathing in category I, 4 questions related to daytime sleepiness in category II, 1 question about high blood pressure, and 1 question regarding BMI in category III. When two of three categories are classified as positive for a patient, the patient is rated as being at high risk of having OSAHS.…”
Section: Introductionmentioning
confidence: 99%